PENGARUH GOOD CORPORATE GOVERNANCE DAN INVESTMENT OPPORTUNITY SET TERHADAP KUALITAS LABA DENGAN STRUKTUR MODAL SEBAGAI VARIABEL INTERVENING (STUDI PADA PERUSAHAAN YANG TERDAFTAR DI SUBSEKTOR INDUSTRI BARANG KONSUMSI PERIODE 2016-2019) - Puspita Mentari; Rokhmawati Andewi; Haryetti Haryetti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This study aims to analyze the effect of good corporate governance, and investment opportunity set on earnings quality through capital structure in companies listed in the Consumer Goods Industry Sub-sector for the 2016-2019 period and selected based on criteria to obtain 120 data. Secondary data was collected by documentation technique by collecting data on independent ownership, managerial ownership, institutional ownership, board of commissioners, audit committee, IOS, DER and earnings quality during the research period in the annual report published on the IDX. The results of the study show that good corporate governance has a positive but not significant effect on capital structure; Investment Opportunity Set has a negative and significant effect on capital structure; good corporate governance has a positive but not significant effect on earnings quality; investment opportunity set has a negative and significant effect on earnings quality; capital structure has a significant negative effect on earnings quality; good corporate governance has a positive but not significant effect on earnings quality by intervening capital structure; investment opportunity set has a negative but not significant effect on earnings quality by intervening capital structure.Keywords: Good Corporate Governance, Investment Opportunity Set, Capital Structure, Earnings Qualit